Oxa–diketopiperazines: Access and Conformational Analysis of Potential Turn Inducers. Issue 21 (24th July 2017) - Berthet, Mathéo; Lebrun, Aurélien; Martel, Arnaud; Cheviet, Thomas; Martinez, Jean; Parrot, Isabelle
Abstract: An improvement of the 1, 2, 5‐oxadiazine‐3, 6‐diones (Oxd) synthesis and reactivity is described in this paper. The methodology has been successfully applied to produce a library of this poorly studied scaffold, which can be considered as an oxa‐diketopiperazine (oxa‐DKP). Significantly, the first crystal structures of oxa‐DKP were obtained and compared to the diketopiperazine ring. Finally, a straightforward procedure concerning the coupling of various amino acids with oxa‐DKP heterocycles to afford original peptidomimetics was reported. The conformational analysis realized on di‐ and tripeptide analogs revealed that the oxa‐DKP skeleton exhibited remarkable β‐turn inducer properties. Abstract : Heterocycles bearing both nitrogen and oxygen as adjacent atoms recently demonstrated a great importance for organic chemists and drug designers. In this context, an efficient access to the underexplored platform 1, 2, 5‐oxadiazine‐3, 6‐diones (Oxd) that could be considered as an oxa‐diketopiperazine was developed. By means of NMR spectrometry, CD analysis and DFT/TDDFT calculations, the obtained oxa‐DKP skeleton exhibited remarkable β‐turn inducer properties when inserted into peptides.